PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN CONTEXTUAL TEACHING AND LEARNING SISWA SEKOLAH DASAR - Murni, Murni; Ismunandar, Ismunandar; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was based on the near extinction of Jepin Tempurung dance in Tanjung Bunga village. The objective achieved in the research was to revitalize Jepin Tempurung dance in order to re exist within a society in Tanjung Bunga village. The method in this research is descriptive. The form of this study is qualitative. The method in this research is the approach to choreography. The data used in this study were interviews, observation, documentation and the results of daily field notes journal about Jepin tempurung dance. The result of this reserch was the effort to revitalize Jepin Tempurung dance by dissecting the from of Jepin Tempurung dance, reenacting Jepin Tempurung dance stard from entering the stage until exiting the stage with music recorded accompaniment, properties and costume Jepin Tempurung.Â Keywords : revitalizazion , Jepin Tempurung dance, Kubu Raya